Bicomponent Cocatalyst Decoration on Flux‐assisted CaTaO2N Single Crystals for Photocatalytic CO2 Reduction under Visible Light. Issue 68 (11th October 2022) - Zhou, Hanghang; Luo, Ying; Xu, Jun; Deng, Lidan; Wang, Zheng; He, Hong
Abstract: Cubic‐like CaTaO2 N photocatalysts with high crystallinity and uniform particle size were successfully prepared by the flux‐assisted nitridation method. The growth of CaTaO2 N single crystals under different synthesis conditions was systematically investigated to understand the effects of the crystallinity and optical property on photocatalytic performance of CO2 reduction. Moreover, the modification of CaTaO2 N single crystals with core‐shell Ni−Ag bicomponent cocatalyst by two‐step decoration process gave a 2.4 times higher amount of CO evolution than the deposition of sole Ag cocatalyst, because of the synergistic effects of bicomponent cocatalyst on the interfacial electron transfer and surface catalytic process. This study provides a valuable way to construct high‐crystalline photocatalysts with effective bicomponent cocatalyst for visible‐light‐driven CO2 reduction with H2 O. Abstract : The well‐defined CaTaO2 N single crystals with uniform particle size were successfully synthesized through a one‐pot NaCl‐assisted nitridation procedure. The performance of photocatalytic CO2 reduction to CO by H2 O under visible light was enhanced due to the high crystallinity of CaTaO2 N and the modification with core‐shell structured Ni−Ag bicomponent cocatalyst.